Perspectivas em Ciência da Informação – v. 19, n. 4 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
Link de acesso ao Número:http://portaldeperiodicos.eci.ufmg.br/index.php/pci/issue/view/123